Implementasi Kedisiplinan dalam Meningkatkan Nilai-Nilai Islam di SMP Negeri 1 Stabat: Studi Kasus Berbasis Pendekatan Kualitatif - Fajar, Ilham Muhammad; Chaniago, Nasrul Syakur (Jurnal Ragam Pengabdian, 2026)
This study aims to examine the implementation of discipline in enhancing Islamic values at SMP Negeri 1 Stabat. Although prior studies have evidenced the significance of Islamic disciplinary programs for character formation, a research gap remains regarding the integration mechanisms within non-Islamic-labeled state schools. This study employs a descriptive qualitative approach with data collection through participatory observation, in-depth interviews, and documentation. Research subjects include the school principal, three Islamic Education (PAI) teachers, two homeroom teachers, and ten students selected via purposive sampling. Source and technique triangulation were applied to ensure data validity, while analysis employed the interactive model of Miles, Huberman, and Saldana (2014). Findings identify four main implementation forms: school regulations grounded in Islamic values, habituation of congregational prayers, pre-class Qur'anic recitation, and teacher exemplary conduct as role models. Results indicate significant positive impacts across four Islamic character dimensions: ritual worship consistency, social moral improvement, academic discipline enhancement, and strengthened intrinsic religious motivation. This study contributes theoretically by integrating Self-Determination Theory (SDT) into an Islamic character education framework, while offering practical implications for state school administrators seeking to systematically implement Islamic values.